An Unusual Group of Ptah-Sokar-Osiris Figures Some Reflections on Typology and Provenance - Rindi Nuzzolo, Carlo.
The present paper investigates an unusual and hitherto unrecognized group of Ptah-Sokar-Osiris figures. Through the study of four rare specimens here presented (first section), a typological analysis of such group is carried out (second section), taking into account their common features (third section) and allowing to establish their possible geographical provenance.